Pendidikan Kemaritiman Anak PAUD melalui Pendekatan Experiential Learning dan STEAM dalam Program Lautku Lestari - Rahmat Olii; Pupung Puspa Ardini; Fiola Indah Putri Pratama (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Low levels of environmental literacy and limited understanding among early childhood learners of the sea’s role as a source of life constitute a major challenge for Early Childhood Education (ECE) institutions in the coastal areas of Gorontalo. This Community Service Program aims to cultivate maritime environmental awareness and pro-environmental behaviors from an early age through an experiential learning approach integrated with the principles of Science, Technology, Engineering, Arts, and Mathematics (STEAM) within the Lautku Lestari program. The activities were implemented by a team of lecturers and students from the Early Childhood Teacher Education Program at Universitas Negeri Gorontalo through hands-on, experience-based learning, designed as a marine-themed carnival and bazaar. Children actively participated in creating works from recycled materials, parading in marine-biota costumes, and engaging in exploratory activities that holistically stimulated the cognitive, affective, and psychomotor domains. Based on structured observations of children’s behavior and participation, the results indicate improved understanding of marine cleanliness and recognition of marine organisms, alongside consistent initial behavioral changes, such as properly disposing of waste, reusing materials during play activities, and identifying simple environmentally friendly actions. Beyond its impact on children, the program produced a marine-themed learning module, eco-friendly educational media, and documentation of best practices in maritime education for ECE. Collaboration among the university, ECE institutions, and the local community emerged as a key factor supporting the program’s success. In terms of sustainability, the program is expected to serve as an adaptive model of maritime education-based community service that can be replicated by other ECE institutions, particularly in coastal regions.ABSTRAKRendahnya literasi lingkungan dan pemahaman anak usia dini terhadap fungsi laut sebagai sumber kehidupan menjadi permasalahan utama yang dihadapi lembaga Pendidikan Anak Usia Dini (PAUD) di wilayah pesisir Gorontalo. Program Pengabdian kepada Masyarakat ini bertujuan menanamkan kesadaran dan perilaku peduli lingkungan maritim sejak usia dini melalui pendekatan experiential learning yang terintegrasi dengan prinsip Science, Technology, Engineering, Arts, and Mathematics (STEAM) dalam Program Lautku Lestari. Kegiatan dilaksanakan oleh tim dosen dan mahasiswa Program Studi Pendidikan Guru Pendidikan Anak Usia Dini Universitas Negeri Gorontalo melalui pembelajaran berbasis pengalaman langsung yang dikemas dalam karnaval dan bazar tematik laut. Anak-anak terlibat aktif dalam pembuatan karya dari bahan daur ulang, parade kostum biota laut, serta aktivitas eksploratif yang menstimulasi aspek kognitif, afektif, dan psikomotor secara terpadu. Hasil kegiatan, berdasarkan observasi terstruktur terhadap perilaku dan partisipasi anak, menunjukkan peningkatan pemahaman tentang kebersihan laut dan pengenalan biota laut, serta munculnya perubahan perilaku awal yang konsisten, seperti kebiasaan membuang sampah pada tempatnya, penggunaan ulang bahan bekas dalam kegiatan bermain, dan kemampuan mengidentifikasi tindakan sederhana yang ramah lingkungan. Selain berdampak pada anak, program ini menghasilkan modul pembelajaran tematik laut, media edukatif ramah lingkungan, serta dokumentasi praktik baik pembelajaran maritim untuk PAUD. Kolaborasi antara perguruan tinggi, lembaga PAUD, dan masyarakat menjadi faktor pendukung keberhasilan program. Secara berkelanjutan, program ini diharapkan menjadi model pengabdian berbasis pendidikan kemaritiman yang adaptif dan dapat direplikasi oleh lembaga PAUD lain, khususnya di kawasan pesisir.